Pengaruh E-Banking Terhadap Kinerja Keuangan Perbankan BUMN yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2020–2024 - Tri Ayu Lestari; Irsad Lubis (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The development of digital technology, particularly mobile banking, can be analogized as the modernization of distribution channels within the logistics industry. In the banking context, the use of mobile banking accelerates transaction flows, increases customer activity volume, and reduces operational burdens that typically arise from branch-based services. These conditions ultimately contribute positively to the improvement of banks’ financial performance through cost efficiency, increased transaction-based income, and the optimization of customer services. This study aims to analyze the effect of e-banking on the financial performance of state-owned banks listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. E-banking is measured using the annual number of e-banking transactions, while financial performance is measured using Return on Assets (ROA). The study employs simple linear regression along with classical assumption tests and hypothesis testing. The results indicate that e-banking has a significant effect on the financial performance of banks.